Effect of Internal Audit and Accounting Information System on the Effectiveness of Internal Control - Marwah Yusuf; Lusiana Kanji (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2020)
This study aims to examine and analyze the effect of internal audit and accounting information systems on the automotive trading company PT. Kars Inti Amanah provides a perspective for the management of similar companies about internal audit and accounting information systems' power to increase internal control effectiveness. The population in this study were all employees of PT. Kars Inti Amanah, amounting to 67 people, were then sampled using a simple random sampling technique so that 40 samples were selected; this study uses a quantitative approach with descriptive statistical analysis to map the value of respondents' answers and multiple lien regression analysis to examine the influence between internal audit variables and accounting information systems on the effectiveness of internal control. The descriptive statistical analysis results show the overall value of the products that internal audit and accounting information systems have a positive and significant effect on the effectiveness of internal control at PT. Kars Inti Amanah.